Using Aquaculture Waste Sludge and Agricultural By-products to Produce Organic Fertilizer - Trung Thanh, Dang; Minh Ty, Nguyen; Huynh Anh Tuyet, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 4, 2024)
The study was conducted to turn aquaculture sludge and agricultural by-products into organic fertilizer as part of the circular production. The main raw materials included sludge from catfish ponds after harvest and organic materials from agricultural by-products (25% from growing cordyceps, 25% from growing oyster mushrooms, 25% from peanut shells, and 25% from coconut fiber). The aquaculture sludge (AS) and agricultural by products (ABP) are mixed at five different ratios: 10% AS + 90% ABP; 30% AS + 70% ABP; 50% AS + 50% ABP; 70% AS + 30% ABP, and 90% AS + 10% ABP. The results showed that the experiment with the ratio of 30% AS + 70% ABP optimized the decomposition of organic compounds and produced organic fertilizer with higher nutrient content than the other four mixing ratios. Comparing the quality of organic fertilizer produced with the organic fertilizer quality standards of the Ministry of Agriculture and Rural Development, 15/18 biochemical indicators have met the regulations. The results of the study can provide a guideline for the local people to optimize organic fertilizer production utilizing aquaculture sludge and agricultural byproducts, save input costs for agricultural production, and contribute to reducing waste to the natural environment.